Penanda Linguistik dalam Penamaan Warung Kopi di Aceh Tengah: Strategi Simbolik untuk Menarik Perhatian Pelanggan - Harfiandi, Harfiandi; Faizi, Ahmad; Hasniyati, Hasniyati; Hutabarat, Imelda; Rosdiana, Rosdiana (Jurnal Ragam Pengabdian, 2026)
The emergence of coffee shops in Central Aceh has spread to every street corner, featuring various forms of name symbols with linguistic markers. It cannot be denied that Central Aceh is known as one of the producers of the highest-quality coffee in the world. Nevertheless, the shop name serves as the primary means of initial recognition as a strategy to attract customers in the competitive coffee market. This study focuses on examining name symbols as strategies based on the concept of linguistic markers in the coffee business. The researcher has examined name symbols from coffee businesses operating in the sub-districts of Bebesen, Lut Tawar, Kebayaken, and Pegasing. This study collected data based on category, character, and language. The results present data in the form of shop name symbols from signboards, along with the reasons behind them, the relationship between the names and the products, and the effects experienced in sales by coffee shop owners. Various forms of linguistic markers demonstrate the existence of reasons that reinforce the journey of the coffee business. Through analysis of interviews, the relationship between the shop’s name and coffee products serves as a business strategy by attracting customer attention as an effort to boost sales. Each product name serves a specific purpose in local, national, and international competitions.